The role of returnee executives in improving green innovation performance of Chinese manufacturing enterprises: Implications for sustainable development strategy. (18th February 2019) - Hao, Yingjie; Fan, Congcong; Long, Yunguang; Pan, Jieyi
Abstract: Environmental problems in China have attracted global attention. Grafting returnee executives' green resources to Chinese manufacturing enterprises is an effective way to solve China's sustainable development problems. This paper focuses on the impact of returnee executives and the heterogeneity of returnee and local executives on green innovation performance and the moderating effects of environmental regulation and managerial ties. The paper builds on data from 276 Chinese manufacturing enterprises. The results show that returnee executives tend to achieve sustainable development through green innovation. However, not all kinds of heterogeneity between returnee and local executives can promote green innovation performance. In addition, environmental regulation and managerial ties, as two important external moderation variables, have different impacts and different extents of impact on the relationship between returnee executives and four aspects (R&D, manufacturing, marketing, and management) of green innovation performance, that is, environmental regulation positively moderates the relationship between returnee executives and green manufacturing and management innovation performance but negatively moderates the relationship between returnee executives and green R&D and marketing innovation performance. These findings have clear management implications for Chinese manufacturing enterprises.